If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -1) + (y + 5) * i = 1 + -3i Reorder the terms: (-1 + 3x) + (y + 5) * i = 1 + -3i Remove parenthesis around (-1 + 3x) -1 + 3x + (y + 5) * i = 1 + -3i Reorder the terms: -1 + 3x + (5 + y) * i = 1 + -3i Reorder the terms for easier multiplication: -1 + 3x + i(5 + y) = 1 + -3i -1 + 3x + (5 * i + y * i) = 1 + -3i -1 + 3x + (5i + iy) = 1 + -3i Reorder the terms: -1 + 5i + iy + 3x = 1 + -3i Solving -1 + 5i + iy + 3x = 1 + -3i Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '3i' to each side of the equation. -1 + 5i + iy + 3i + 3x = 1 + -3i + 3i Reorder the terms: -1 + 5i + 3i + iy + 3x = 1 + -3i + 3i Combine like terms: 5i + 3i = 8i -1 + 8i + iy + 3x = 1 + -3i + 3i Combine like terms: -3i + 3i = 0 -1 + 8i + iy + 3x = 1 + 0 -1 + 8i + iy + 3x = 1 Add '1' to each side of the equation. -1 + 8i + iy + 1 + 3x = 1 + 1 Reorder the terms: -1 + 1 + 8i + iy + 3x = 1 + 1 Combine like terms: -1 + 1 = 0 0 + 8i + iy + 3x = 1 + 1 8i + iy + 3x = 1 + 1 Combine like terms: 1 + 1 = 2 8i + iy + 3x = 2 Add '-3x' to each side of the equation. 8i + iy + 3x + -3x = 2 + -3x Combine like terms: 3x + -3x = 0 8i + iy + 0 = 2 + -3x 8i + iy = 2 + -3x Reorder the terms: -2 + 8i + iy + 3x = 2 + -3x + -2 + 3x Reorder the terms: -2 + 8i + iy + 3x = 2 + -2 + -3x + 3x Combine like terms: 2 + -2 = 0 -2 + 8i + iy + 3x = 0 + -3x + 3x -2 + 8i + iy + 3x = -3x + 3x Combine like terms: -3x + 3x = 0 -2 + 8i + iy + 3x = 0 The solution to this equation could not be determined.
| 3x+y+5*4i=2 | | 10(d+4)=40 | | 12-(4x-3)=30 | | 32=17 | | 3(2y-7)=9 | | 6-9x=-3 | | -(x-9)=-x-9 | | -(x-7)=-x-7 | | 3x-(5x-(105-30x)-35)=12 | | 8x+16=56-2x | | lg(2x)=-1 | | 24=8x+6y | | 9-4y=-5y | | 41+13x=37+8x+8 | | 0,1x-10=30 | | 5(3w+7)=-32 | | X^2=1.93 | | 4534543534534+4353434534= | | x(x-5)=176 | | (x-5)(x+4)=(x+7)(x-6) | | 3w+7=-6.4 | | 2k=-f-t | | 7-2x(x+4)=14+5x | | t=2k-f | | p=b+2d | | 3x*4x=600 | | 3x*4X=24 | | 7x+21y=28 | | 2x+4=-8-4x | | 2x-x+30=80 | | 2x*5+6=3 | | 2x*11=3 |